2018
DOI: 10.1158/0008-5472.can-17-2143
|View full text |Cite
|
Sign up to set email alerts
|

A20/TNFAIP3 Regulates the DNA Damage Response and Mediates Tumor Cell Resistance to DNA-Damaging Therapy

Abstract: A competent DNA damage response (DDR) helps prevent cancer, but once cancer has arisen, DDR can blunt the efficacy of chemotherapy and radiotherapy that cause lethal DNA breakage in cancer cells. Thus, blocking DDR may improve the efficacy of these modalities. Here, we report a new DDR mechanism that interfaces with inflammatory signaling and might be blocked to improve anticancer outcomes. Specifically, we report that the ubiquitin-editing enzyme A20/TNFAIP3 binds and inhibits the E3 ubiquitin ligase RNF168, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Chromatin extraction was performed as previously described (49). The cells were lysed in 100 l of chromatin extraction buffer A (10 mM PIPES, 300 mM sucrose, 100 mM NaCl, 3 mM MgCl 2 , 1 mM EGTA, 0.2% Triton X-100, pH 6.8) on ice.…”
Section: Chromatin Extraction Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…Chromatin extraction was performed as previously described (49). The cells were lysed in 100 l of chromatin extraction buffer A (10 mM PIPES, 300 mM sucrose, 100 mM NaCl, 3 mM MgCl 2 , 1 mM EGTA, 0.2% Triton X-100, pH 6.8) on ice.…”
Section: Chromatin Extraction Assaymentioning
confidence: 99%
“…His-tagged proteins were also expressed in E. coli BL21 cells and purified using a Ni 2ϩ -Sepharose affinity column (GE Healthcare). In vitro pulldown assays were performed as described previously (49).…”
Section: Protein Purification and In Vitro Pulldownmentioning
confidence: 99%
See 1 more Smart Citation
“…The zinc finger domain of A20 targets TRAF2 for lysosomal degradation [98]. Yang et al found that A20 regulates the DNA damage response and mediates tumor cell resistance to DNA damage therapy [99].…”
Section: A20mentioning
confidence: 99%
“…TNFAIP3 mutations were also identified in this study at a higher frequency than prior reports (60% in NSHL) (Reichel et al , ). TNFAIP3 encodes an ubiquitin‐converting enzyme of the NF‐κB pathway, and loss of function mutations was recently linked to lower efficacy of chemotherapy (Yang et al , ). By whole exome sequencing, Tiacci et al () found that over 80% of patient samples carry mutations in the JAK/STAT pathway.…”
Section: The Genomic Landscapementioning
confidence: 99%